Memories of Inhabiting: Living Conditions at Work in Textile Factories in San Agustín Etla Oaxaca - López-Oliver-Farías, Rosa María (Corporación Universitaria del Caribe, CECAR., 2021)
The objective of this research was to rescue and analyze the memories of inhabiting. A historical search was carried out on the feeling of belonging of the workers in the manufacturing sector, starting from their past. For this, in-depth interviews were carried out under a deductive scheme of those people who lived and participated as workers in the textile yarn and fabric factories of San José and Soledad Vista Hermosa. This research was carried out from 2018 to 2019, in the community of San Agustín, located in the central part of the State of Oaxaca, in the Central Valley Region, belonging to the Etla District.